Food Security In Romania - Andreea D. GIUCA; Claudiu F. LACEANU (Communications of International Proceedings, 2021)
The aim of the research is to analyze the current situation and future prospects for sustainable food security in Romania, given several EU concerns about food security became more frequent during the debates on the future of the Common Agricultural Policy in 2014-2020 and have were used as an argument in favor of maintaining the CAP as a strong and integrated policy. In this respect, it has been established that food security for the population must be the most important objective of the CAP. The main research methods used in the study were the use of national and international statistics on the production and consumption of agri-food products, these data were analyzed using statistical indicators such as: standard deviation, coefficient of variation and annual growth rate. The study identified that the issue of food security has become paramount, due to increasing demand for food. At present, the countries of the European Union do not face major problems in terms of food security, in terms of food availability and supply, but the income gaps and the poor development of some countries, which lead to a decline in food security. certain sections of the population can raise problems in terms of population access to food and can affect food security in some poorer EU Member States, such as Romania where vulnerability to food insecurity is due to the differential between living conditions. urban and rural environment.
Keywords: food security; agricultural production; consumption; climate change; food waste